Методы и информационная технология разработки мобильных лечебно-диагностических комплексов - Тимашов, Е.А. (Комп’ютерні засоби, мережі та системи, 2016)
Analyzed the requirements for software and hardware of mobile medical devices and information technology of their creation is considered.